2021
DOI: 10.1002/tea.21726
|View full text |Cite
|
Sign up to set email alerts
|

“Well that's how the kids feel!”—Epistemic empathy as a driver of responsive teaching

Abstract: While research shows that responsive teaching fosters students' disciplinary learning and equitable opportunities for participation, there is yet much to know about how teachers come to be responsive to their students' experiences in the science classroom. In this work, we set out to examine whether and how engaging teachers as learners in doing science may support responsive instructional practices. We draw on data from a year-long blendedonline science professional development (PD) program that began with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…These findings also extend prior research on teachers' noticing by demonstrating the integrated nature of teachers' awareness of multiple features of classroom interactions. While there is value in distinguishing the objects of teachers' noticingsuch as noticing epistemic affect or noticing student thinking (Jaber, 2016;Luna, 2018) research also finds that teachers who enact equitable and responsive teaching attend to a variety of aspects of their students and classroom interactions (Kang, 2021;van Es et al, 2022). With a greater imperative to move mathematics and science instruction toward equitable teaching and learning, important questions for future inquiry concern how teachers' noticing of student thinking is integrated with other features of classroom interactions, such as how students come to be positioned to have agency in their learning as teachers come to interpret students' thinking from anti-deficit, strengthsbased perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also extend prior research on teachers' noticing by demonstrating the integrated nature of teachers' awareness of multiple features of classroom interactions. While there is value in distinguishing the objects of teachers' noticingsuch as noticing epistemic affect or noticing student thinking (Jaber, 2016;Luna, 2018) research also finds that teachers who enact equitable and responsive teaching attend to a variety of aspects of their students and classroom interactions (Kang, 2021;van Es et al, 2022). With a greater imperative to move mathematics and science instruction toward equitable teaching and learning, important questions for future inquiry concern how teachers' noticing of student thinking is integrated with other features of classroom interactions, such as how students come to be positioned to have agency in their learning as teachers come to interpret students' thinking from anti-deficit, strengthsbased perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Walkoe et al (2022) show that elementary students have preliminary ideas about algebra in early grades and support teachers identifying and reasoning about students' early algebraic thinking. Relatedly, Jaber (2016) found that participating in professional development to promote responsiveness to students' science thinking supported one teacher's noticing and responding to student thinking, as well as increased awareness of his students' epistemic affect as an integral part of their engagement in science. This finding is similar to Kang (2021) who documented a novice teacher's efforts to enact responsive and equitable science instruction and found that this teacher attended to the intellectual, relational, and linguistic challenges that students experienced in the lesson.…”
Section: Expanding Conceptions Of Noticing For Responsive Teachingmentioning
confidence: 99%
“…Due in part to such epistemological commitments, this study displays tensions in creating student-centered learning opportunities by laboratory instructors. As such, future research could alleviate such tensions by focusing on teacher-scientist partnerships that help laboratory instructors develop epistemic empathy (Jaber et al, 2022), while also creating mutualistic relationships that cultivate respect for the experiences of both future teachers and scientists (Atias et al, 2023;Shanahan & Bechtel, 2020). Teacher-scientist partnerships can be cultivated such that future teacher candidates can develop insight into the challenges scientists face when generating and building upon ideas when trying to make sense of phenomena.…”
Section: Implications For Instructionmentioning
confidence: 99%
“…2 describes our coarse model for teachers' experiencing and responding to epistemological messages. Black circles represent possible sources of epistemological messages, black (Jaber et al, 2022).…”
Section: Centering Teachers' Responses To Epistemological Messagesmentioning
confidence: 99%